Optimizing the structure of interdisciplinary tumor boards for effective cancer care - Braulke, Friederike; Kober, Kathrin; Arndt, Andreas; Papendick, Maximilian; Strauss, Arne; Kramm, Christof Maria; Thoms, Kai-Martin; König, Alexander; Gaedcke, Jochen; Gallwas, Julia; Wulf, Svenja; Szuszies, Christoph; et al. (Frontiers in Oncology, 2023)
Multi-professional interdisciplinary tumor boards (ITB) are essential institutions to discuss all newly diagnosed, relapsed or complex cancer patients in a team of specialists to find an optimal cancer care plan for each individual patient with regard to national and international clinical practice guidelines, patient´s preference and comorbidities. In a high-volume cancer center, entity-specific ITBs take place at least once a week discussing a large number of patients. To a high level of expertise and dedication, this also requires an enormous amount of time for physicians, cancer specialists and administrative support colleagues, especially for radiologists, pathologists, medical oncologists and radiation oncologists, who must attend all cancer-specific boards according to certification requirements. In this 15-month prospective German single-center analysis, we examined the established structures of 12 different cancer-specific ITBs at the certified Oncology Center and demonstrate tools helping to optimize processes before, during and after the boards for optimal, time-saving procedures. By changing pathways, introducing revised registration protocols and new digital supports we could show that the workload of preparation by radiologists and pathologists could be reduced significantly by 22.9% (p=<0.0001) and 52.7% (p=<0.0001), respectively. Furthermore, two questions were added to all registration forms about the patient´s need for specialized palliative care support that should lead to more awareness and early integration of specialized help.